Histone acetylation-independent transcription stimulation by a histone chaperone - Kato, Kohsuke (Oxford University Press, 2007)
Histone chaperones are thought to be important for maintaining the physiological activity of histones; however, their exact roles are not fully understood. The physiological function of template activating factor (TAF)-I, one of the histone chaperones, also remains unclear; however, its biochemical properties have been well studied. By performing microarray analyses, we found that TAF-I stimulates the transcription of a sub-set of genes. The transcription of endogenous genes that was up-regulated by TAF-I was found to be additively stimulated by histone acetylation. On performing an experiment with a cell line containing a model gene integrated into the chromosome, TAF-I was found to stimulate the model gene transcription in a histone chaperone activity-dependent manner additively with histone acetylation. TAF-I bound to the core histones and remodeled the chromatin structure independent of the N-terminal histone tail and its acetylation level in vitro. These results suggest that TAF-I remodel the chromatin structure through its interaction with the core domain of the histones, including the histone fold, and this mechanism is independent of the histone acetylation status.